THE INFLUENCE OF TAX BILLING BY FORCED LETTER INTENSITY AGAINST TAXPAYER COMPLIANCE IN TAX SERVICE OFFICE ‘PRATAMA’ MANADO - Kawulur, Cecilya Helmy; Pangemanan, Sifrid (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Tax Billing by forced letter is the government's efforts to improve the welfare of the people and encourage people to be responsible and participate in economic development. This study aims to determine the influence of tax billing by forced letter intensity against taxpayer compliance in Tax Service Office ‘Pratama’ Manado. The analysis method used in this research is associative research methods to describe the influence of tax billing by forced letter intensity against taxpayer compliance in Tax Service Office ‘Pratama’ Manado. The research result revealed that there are significant of the intensity of the implementation of tax influence billing by forced letter to tax compliance at Tax Service Office ‘Pratama’ Manado. The leaders of Tax Service Office ‘Pratama’ Manado should provide a good service to push the participation taxpayers in paying taxes. Keywords: tax billing by forced letter, taxpayer compliance